Moderating effect of partner smoking on pregnant women's intention to stop smoking: applying the reasoned action approach. (1st November 2020) - Middlestadt, Susan E.; Macy, Jonathan T.; Dowty, Rachel; Arrieta, Alejandro; Jay, Stephen J.
Abstract: Background: Pregnant women are a priority for cessation interventions. Guided by the Reasoned Action Approach, this study tested whether partner's smoking status moderated the effects of attitude, perceived norm, and perceived behavioral control on intention to take measures to quit smoking among a sample of pregnant women. Methods: Women ( N = 288) who reported smoking were recruited during their first prenatal visit to a clinic-based intervention study. Clinic staff referred potentially eligible women to study staff who confirmed eligibility and conducted a baseline survey. Multiple linear regression analyses examined the effect on intention of attitude, perceived norm, perceived behavioral control, age, nicotine dependence, and partner smoking as well as two-way interactions between partner smoking and attitude, perceived norm, and perceived behavioral control. Results: Perceived behavioral control (β = .536, p = .000) and perceived norm (β = .233, p = .000) were significantly associated with intention to stop smoking. There were no significant effects of attitude, age, nicotine dependence, or partner smoking. The main effect of perceived norm was modified by an interaction with partner's smoking status (β = .365, p = .009). Probing this interaction revealed that the weight for perceived norm was statistically significant for women with a smoking spouse or romantic partner (β = .356, p = .000) but not for women without one (β= −.006, p = .955). Conclusions: Interventions for pregnant smokers should focus on increasing perceived behavioral control to take measures to stop either by improving perceived skill or by modifying the environment to make stopping easier. Perceived norm can be a useful target for change, but only for women with romantic partners who smoke cigarettes.